2017
DOI: 10.3389/fmicb.2017.00696
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Mode of Action of the Sactibiotic Thuricin CD

Abstract: Thuricin CD is a two-component bacteriocin, consisting of the peptides Trnα and Trnβ, and belongs to the newly designated sactibiotic subclass of bacteriocins. While it is clear from studies conducted thus far that it is a narrow-spectrum bacteriocin, requiring the synergistic activity of the two peptides, the precise mechanism of action of thuricin CD has not been elucidated. This study used a combination of flow cytometry and traditional culture-dependent assays to ascertain the effects of the thuricin CD pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…It has been shown that subtilosin A binds to the cell membrane and creates transient pores, thereby leading to an efflux of intracellular ions and ATP and eventually to cell death . Similar observations have also been made for the two‐component sactibiotic thuricin CD . However, thuricin H shows a distinct mode of action and does not bind cell membranes or result in any detectable changes in membrane permeability .…”
Section: Figuresupporting
confidence: 80%
“…It has been shown that subtilosin A binds to the cell membrane and creates transient pores, thereby leading to an efflux of intracellular ions and ATP and eventually to cell death . Similar observations have also been made for the two‐component sactibiotic thuricin CD . However, thuricin H shows a distinct mode of action and does not bind cell membranes or result in any detectable changes in membrane permeability .…”
Section: Figuresupporting
confidence: 80%
“…A recent mode of action study has shown that thuricin CD inserts into the membrane of the target cell, forms pores, and causes ion leakage, membrane depolarization, and finally, cell lysis. 54 Structural elucidation studies of thuricin CD have shown that each of the two components contains three sactionines. The linkages in Trnα are from Cys5, Cys9, and Cys13 to Thr28, Thr25, and Ser21, respectively.…”
Section: Ripp Biosynthetic Reactions Catalyzed By Rsam Enzymesmentioning
confidence: 99%
“…These peptides are thought to act by creating pores in the bacterial membrane, causing an inux of ions that leads to membrane depolarization and cell death. 153,154 Subtilosin A, produced by strains of Bacillus subtilis, was the rst sactipeptide to be identied and characterized ( Fig. 3a).…”
Section: Colonization Resistance To Pathogenic Microbesmentioning
confidence: 99%
“…151,152 Subtilosin A demonstrates relatively broad bacteriocidal activity against Gram-positive pathogenic bacteria implicated in bacterial vaginosis, food poisoning, and hospital infections, including Gardnerella vaginalis, Listeria monocytogenes, Enterococcus faecium, and Staphylococcus aureus. 153,158,159 Other sactipeptides have been isolated exclusively from gut microbes, such as thuricin CD 154,[160][161][162] (Fig. 3a) and thurincin H 163,164 (Fig.…”
Section: Colonization Resistance To Pathogenic Microbesmentioning
confidence: 99%